2019
DOI: 10.3389/fimmu.2019.00496
|View full text |Cite
|
Sign up to set email alerts
|

Defective Localization With Impaired Tumor Cytotoxicity Contributes to the Immune Escape of NK Cells in Pancreatic Cancer Patients

Abstract: Tumor-infiltrating lymphocytes (TILs), found in patients with advanced pancreatic ductal adenocarcinoma (PDAC), are shown to correlate with overall survival (OS) rate. Although majority of TILs consist of CD8 + /CD4 + T cells, the presence of NK cells and their role in the pathogenesis of PDAC remains elusive. We performed comprehensive analyses of TIL, PBMC, and autologous tumor cells from 80 enrolled resectable PDAC patients to comprehend the NK cell defects with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 57 publications
(44 reference statements)
2
89
0
Order By: Relevance
“…TGF‐β1 inhibits cytokine secretion and cytotoxicity of NK cells [15–18,27]. NK cell function was impaired, which had been widely observed in patients with advanced cancer [29–31]. Consistent with previous data, we found that plasma TGF‐β1 levels were obviously elevated in patients with HCCBC, albeit only slightly higher in adjacent tumor tissues than in tumors and healthy tissues.…”
Section: Discussionsupporting
confidence: 90%
“…TGF‐β1 inhibits cytokine secretion and cytotoxicity of NK cells [15–18,27]. NK cell function was impaired, which had been widely observed in patients with advanced cancer [29–31]. Consistent with previous data, we found that plasma TGF‐β1 levels were obviously elevated in patients with HCCBC, albeit only slightly higher in adjacent tumor tissues than in tumors and healthy tissues.…”
Section: Discussionsupporting
confidence: 90%
“…Aside from that, it has been found that the abundance of activated pancreatic stellate cells in the stroma of pancreatic cancer can diminish NK cell functions in the local tumor microenvironment [ 91 ]. Moreover, it was demonstrated that PDAC-NK cells exhibit an impaired tumor localization that was associated with the downregulation of the chemokine receptor CXCR2 [ 92 ]. Therefore, PDAC tumors show an extremely low frequency of NK cell infiltration (<0.5%) counteracting tumor cell elimination.…”
Section: Contribution Of Natural Killer (Nk) Cells In Pdacmentioning
confidence: 99%
“…Therefore, PDAC tumors show an extremely low frequency of NK cell infiltration (<0.5%) counteracting tumor cell elimination. Of note, the in vitro proliferation rate of isolated tumor-infiltrating NK cells was associated with a longer overall survival [ 92 ].…”
Section: Contribution Of Natural Killer (Nk) Cells In Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the response of patients with PDAC to immunotherapy is overall limited [ 6 ]. However increasing pieces of evidence suggest that the restoration of NK cell activity in the tumor microenvironment (TME) may interfere with PDAC progression [ 7 , 8 ] exerting direct cytotoxicity and orchestrating the anti-tumor immune response.…”
Section: Introductionmentioning
confidence: 99%